Understanding the unusual fluidity characteristics of high ash Indian bituminous coals - Das, Bidyut; Suresh, A; Dash, P.S.; Chandran, S.; Castro-Díaz, M.; Stevens, Lee A.; Snape, Colin E. (Elsevier, 2018)
High-temperature rheometry and 1H nuclear magnetic resonance (NMR) are two complementary techniques that have been used to investigate fluidity development quantitatively in the < 53 µm and 53-212 µm size fractions of high ash Indian non-coking coals and imported non-coking, medium coking and good coking coals. It was found for the 53-212 µm size fraction of the Indian bituminous coal with higher ash content (30 wt%) that, despite its high complex viscosity (> 105 Pa.s), the maximum concentration of fluid H was quite similar to that of the good coking coal (40%). This Indian non-coking coal developed fluid H with the greatest mobility (T2L > 150 μs) in the coal series, regardless of the particle size fraction studied. The probable explanation for this abnormal behavior is that the mineral matter prevents bulk movement in the sample but the local mobility of the fluid phase is still high on the nanometer scale. Blending the two Indian non-coking coals with the highly fluid medium coking coal gave higher viscosities (i.e. lower fluidity) than predicted by the polymer blend rule, probably again due to the high mineral matter restricting bulk flow. This negative effect was less pronounced with the higher ash coal suggesting that the high mobility of the fluid entities in this coal might prevent the destruction of fluid entities evolving from the medium coking coal. Partial demineralization of the high ash Indian non-coking coal to 17 wt% through a sink-float method did not decrease the complex viscosity of this coal but reduced the maximum mobility of the fluid H to levels observed with the lower ash content (20 wt%) Indian coal. Therefore, this reduction in mobility could be directly related to the mineral matter in the Indian non-coking coal.